Nursing experience of geriatric syndromes in an elderly patient (1例老年综合征患者的护理体会) - ZHANG Yajie (张亚杰); DAI Hui (戴晖) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the nursing experience of geriatric syndromes in an elderly patient. In the clinical nursing, it is required to determine the health conditions by using comprehensive geriatric assessment, adopt case management suitable for the elderly, provide integrative healthcare service, and improve the functional status and quality of life in elderly patients. (本文总结了1例老年综合征患者的护理经验, 在临床工作中科学运用老年综合评估明确老年患者的健康问题, 采用适合老年人的个案管理的模式, 为老年患者提供整体化的健康服务, 从而促进老年患者达到最佳的功能状态, 提高老年人的生活质量。)